Perfectionism, Burnout and Extracurricular Activities Among Medical Students from the University of Coimbra - Dinis, Tomás (2020)
Introduction: The participation in extracurricular activities reduces the attributed importance to some causes of perfectionism, which influences the prevalence of burnout in medical students. This study aimed to investigate how this relationship occurs and which factors it is dependent on, in order to create strategies directed at these potential targets.Material and Methods: We developed a questionnaire that assesses the participation in extracurricular activities, including a survey regarding the reasons for perfectionism and part of the Copenhagen Burnout Inventory adapted for students. The questionnaire’s application to medical students of the Masters Degree in Medicine of the Faculty of Medicine, University of Coimbra was followed by statistical analysis.Results: In a sample of 360 students, 40% ranked highly in personal burnout, and 28.1% in study-related burnout, while 22.2% showed high levels of burnout in both components. Students who participated in extracurricular activities were less frequently associated with simultaneous personal-related and study-related high levels of burnout (p = 0.013). The kind of chosen extracurricular activity was notassociated with the prevalence of burnout.Discussion: Only 53.9% of students participate in extracurricular activities. Such participation is associated with a lower prevalence of burnout if it is practiced several times per week. The choice of one kind of activity over another does not seem to influence the prevalence of this syndrome, all of which are associated with benefits in different domains.Conclusion: We observed a lower prevalence of burnout among students that engaged in extracurricular activities. Further studiesthat can infer causality in this relationship are needed, in order to establish effective solutions specific to the medical course context.